A Cultural Content Analysis of The 2018 Indonesian Ministry of Education and Culture-Published English Textbook "Bahasa Inggris" for 12th-Grade Students - Irawati, Ratna; Syamsudin, Syamsudin; Diana, Diana (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This study aims to answer the questions related to the Cultural perspective including cultural categories from Cortazzi and Jin (1999) and cultural dimension from Moran (2001). To answer these questions, descriptive qualitative analysis was used. This research focused on the English student textbook "Bahasa Inggris," published by the Indonesian Ministry of Education and Culture in 2018 for the 12th Grade of Senior High School. The data was collected through reading, comprehending, analyzing, and gathering information from books and in-depth interview with students, as well as through focus group discussions with fellow teachers. The analysis indicates that the "Bahasa Inggris" textbook for twelfth-grade students effectively incorporates cultural perspectives from Cortazzi and Jin (1999) as well as cultural dimensions from Moran (2001). This textbook serves a valuable tool for enhancing students' cultural awareness by encompassing Cultural Content from Cortazzi and Jin (1999), such as Source Culture, Target Culture, and International Culture, and Cultural Dimensions from Moran (2001), including Products, Practices, Perspectives, Communities, and Persons, thereby enriching students' cultural understanding through content and personal experiences. Therefore, the textbook is well-suited for senior/vocational high school twelfth-graders. It enhances students' comprehension of everyday life and cultural facets, making it an invaluable resource for teaching and learning. However, there is a need for substantial improvements to effectively address its weaknesses.